The high latitude convection response to an interval of substorm activity - T. K. Yeoman; M. Pinnock
On 17 March 1991, five clear substorm onsets/intensifications took place within a three hour interval. During this interval ground-based data from the EISCAT incoherent scatter radar, a digital CCD all sky camera, and an extensive array of magnetometers were available, in addition to data from the CRRES and DMSP spacecraft, whose footprints passed over Scandinavia very close to most of the ground-based instrumentation. This interval of substorm activity has been interpreted as being in support of a near-Earth current disruption model of substorm onset. In the present study the ionospheric convection response, observed some four hours to the west in MLT by the Halley HF radar in Antarctica, is related to the growth, expansion and recovery phases of two of the substorm onsets/expansions observed in the Northern Hemisphere. Bursts of ionospheric flow and motion of the convection reversal boundary (CRB) are observed at Halley in response to the substorm activity and changes in the IMF. The delay between the substorm expansion phase onset and the response in the CRB location is dependent on the local time separation from, and latitude of, the initial substorm onset region. These results are interpreted in terms of a synthesis of the very near-Earth current disruption model and the near-Earth neutral line model of substorm onset.